Pedagogical alternative from the south: dialogue between Paulo Freire, Frantz Fanon and Boaventura de Sousa Santos (Praxis Educativa, 2022)
This essay aims to establish a dialogue between the pedagogical contributions of Paulo Freire, Frantz Fanon and Boaventura de Sousa Santos, with the purpose of claiming the collective construction of a pedagogical alternative that from the south provokes indignation, promotes ecological awareness and instills a social role. If the pedagogy that promotes modernity has as its main characteristic the dehumanization of the human being, the pedagogical alternative from the south will have its humanization as its goal. This is the power that counter-hegemonic education keeps within itself. Through the pedagogical postulates of these three intellectuals, the aim is to become aware of what modernity denied us for centuries: the possibility of creating anti-colonial, anti-capitalist and anti-patriarchal subjectivities.
Keywords: Education, epistemological tensions, transformation.